The effect of work accidents on the efficiency of production in the coal sector - Ya şar Kasap (South African Journal of Science, 2011)
In comparison with other sectors, mining is one of the sectors with the highest rates of work accidents. Such accidents negatively affect a country's economy by wasting domestic resources and causing losses of both labour force and working days. What distinguishes mining from other branches of industry is that its working environments change continually and the working conditions are particularly harsh. Because of the practice of labour-intensive underground production methods, which leads to an increase in risk factors in terms of work accidents, and the fact that coal is a leading resource in meeting the ever-increasing demand for energy, this study investigated how work accidents affected the efficiency of production in the Turkish Hard Coal Enterprise (TTK) between 1987 and 2006. Using data envelopment analysis, the overall sources of technical inefficiency in the years examined were determined. The results from this analysis revealed that the overall technical efficiency was as low as 69.7%, particularly as a result of the disaster in 1992; work accidents therefore had a negative effect on production efficiency. The greatest degree of pure technical inefficiency was found to have occurred in the period between 1992 and 2000, when the highest number of work accidents were noted, whilst the greatest degree of scale inefficiency was found to have occurred between 1987 and 1993. Because TTK has a prominent position among institutions and attaches great importance to workers' health and safety, an increase was noted in efficiency scores after 1993.